Development of the “Wander Expression” Booklet as an Innovative Media Guide for Classical Guidance Service to Enhance Students’ Social-Emotional Skills - Tria Putri Ayu Arisona; Asieline Wahyu Tri Ardyanti; Budi Purwoko; Evi Winingsih (STAI Auliaurrasyidin Tembilahan, 2026)
This study investigates the development of the Wander Expression Booklet as an innovative media guide to support school counselors in delivering classroom guidance services aimed at enhancing students’ social-emotional skills. The study employed a Research and Development (R&D) approach using the 4D Development Model, which consists of the Define, Design, Develop, and Disseminate stages (Thiagarajan, Semmel, & Semmel, 1974). The research subjects were school counselors at a secondary school in Surabaya, Indonesia. Data were collected through observations, interviews, and validation questionnaires administered to content experts, media experts, and prospective users. Data analysis was conducted using qualitative descriptive techniques with score conversion into feasibility categories. The validation results demonstrated that the Wander Expression Booklet achieved feasibility scores of 94% from content experts, 94% from media experts, and 90% from prospective users, all categorized as highly feasible. Product revisions were implemented based on expert feedback, including refinement of the title, strengthening of social-emotional content, and the addition of visualized media implementation procedures. A limited trial conducted at SMP Negeri 28 Surabaya indicated increased student engagement, enthusiasm, and understanding in recognizing and regulating emotions appropriately. Based on these findings, the Wander Expression Booklet is considered valid, practical, and effective as a media guide for classroom guidance services in secondary schools.